Dracula - Rice, Chris, 1952- (Penguin readers. Level 3, Pre-intermediate, 2000)
"Count Dracula is a vampire. He drinks people's blood. He lives in a lonely castle in the mountains of Transylvania. But the he comes to England ... Professor van Helsing knows about vampires, but can he stop Dracula?" --contratapa.